Whom should you believe?: strategies of counsels and witnesses in a Malaysian courtroom - Noraini Ibrahim, (Fakulti Undang - Undang, 2011)

(untitled)
In our Malaysian adversarial criminal judicial system, cross-examinations are essentially hostile. Lawyers will test the credibility of the evidence of witnesses with questions that will attempt to discredit the adverse party, while at the same time, attempting to strengthen their side. Witnesses who are being cross-examined will be made aware of these objectives and will attempt to preserve their version. This article, which is based on a case study of a criminal trial, will attempt to show how witnesses and lawyers employ certain strategies to challenge versions of reality in order to present and preserve their alternative version